The relationship between grammatical knowledge and reading comprehension: A meta-analysis - Zheng, Haoyuan; Miao, Xuecong; Dong, Yang; Yuan, Daniel-Chongbo (Frontiers in Psychology, 2023)
To examine the cohesive tie effect on reading comprehension through the grammatical knowledge cognition process. The present meta-analysis examined the correlation between grammatical knowledge and reading comprehension based on empirical results published between 1998 and 2021. This study selected 86 studies with a total of 14852 readers whose grades were grouped from primary school to university. Results showed that the overall correlation effect size between grammatical knowledge and reading comprehension was large, and the significant interaction effect of grade group was confirmed through moderator analysis. Results suggested the grammatical knowledge’s function of the cohesive tie has a transfer effect across different text comprehension scripts.